Prevalence and Factors Associated With the Management of Tungiasis in Ikolomani Sub-County, Kakamega County, Western Kenya - Owino, Perez; Onguru, Daniel; Ayodo, George (East African Medical Journal, 2024)
Background: Tungiasis is a neglected tropical disease caused by skin penetration by female jigger fleas, predominantly Tunga penetrans, most commonly in resource-limited settings with sub-optimal basic hygiene standards, mainly in developing countries. Objective: We investigated the factors associated with tungiasis management in Ikolomani Sub County, Kakamega County in Western Kenya. Design: Descriptive study using mixed-methods approach, involving clinical observation, questionnaire, and environmental observation. Setting: Ikolomani Sub-County, Kakamega County, Western Kenya Participants: tungiasis patients identified at community. Outcome measures: Quantitative data underwent descriptive and inferential analysis (α = 0.05) using SPSS v.23, qualitative data was analyzed thematically. Results: Overall Tungiasis prevalence was 65% (95% CI: 60–70%), Idakho South and Idakho North recording the highest prevalence. Toes and soles were the most common sites of infestation. Only 91(34.5%) respondents sought medical treatment. Thorns (13.9%) and hydrogen peroxide (15.2%) were the common methods for jigger extraction. Residents from Idakho Central (aOR 0.44, 95%CI (0.23-0.83)) and Idakho East (aOR 0.43, 95%CI (0.22-0.85)) were less likely to suffer from tungiasis than those from Idakho North. Those with previous tungiasis were 7.24 times (aOR 7.24, CI (4.54-13.9)) more likely to be infested. Good/ hospitable healthcare staff was the major reason for choice of treatment. Sleeping on the floor was the main cause of tungiasis and its manifestation presents as a painful swelling. The major intervention of tungiasis was to remove them as mentioned by the participants. Spraying of animals was the preventive measure for Tungiasis. Conclusion: Residence and previous jigger infestation were independently associated with tungiasis infestation. Stigma, discrimination, and difficulty wearing shoes were some of the major challenges faced by tungiasis patients. Recommendation: There is need for enhanced intervention and health education in Ikolomani Sub County community on risk factors and management of tungiasis.